Peculiarities of Law Training of the Junior Teenagers of Boarding Schools - Olena Polishchuk (Pedagogical Discourse, 2013)
The author of the article examines the specificity of law training of the junior teenagers of general educational boarding schools. The attention is accented on social-pedagogical rehabilitation as one of the conditions of increase of the effectiveness of law training of the junior teenagers of boarding schools. Its application in the process of law training of the junior teenagers under the conditions of establishments of boarding school type is shown. The functions of the legal training teenagers of the boarding schools as for the social-pedagogical rehabilitation have been determined: compensational, diagnostic-prognostic, adaptational, correctional, and preventive. Methodic recommendations to the pedagogues of general educational boarding schools as for effective organization of the legal training of the junior teenagers have been offered.